A catalyst for ethylene glycol fuel cell and its preparation method

By using materials such as melamine phosphate in ethylene glycol fuel cell catalysts to synthesize COFs, and introducing platinum, cobalt and iron atoms at high temperatures to form a stable PtCoFe-N-C structure, the existing catalysts have been solved, and an efficient and stable ethylene glycol oxidation reaction has been achieved.

CN118472284BActive Publication Date: 2025-03-11YANCHENG TEACHERS UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410679883.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-29
Publication Date
2025-03-11
Estimated Expiration
2044-05-29

AI Technical Summary

Technical Problem

The existing ethylene glycol fuel cell catalysts are costly and have weak anti-toxicity, making it difficult to introduce non-Pt substances into precious metal catalysts to reduce costs while maintaining good catalytic performance.

Method used

The COFs materials were synthesized by ultrasonic using melamine phosphate, trialdehyde phlogenes, 1,3,5-tris(4-aminophenoxy)benzene and SiOx@C preproducts, and platinum, cobalt and iron atoms were introduced at high temperature to form a stable PtCoFe-N-C structure, improving the activity and stability of the catalyst.

Benefits of technology

The prepared catalyst has a high specific surface area, rich active sites and good electron transport channels, which significantly improves the electrocatalytic activity of the ethylene glycol oxidation reaction, reduces the use of precious metals, reduces the production cost, and improves the stability of the catalyst.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a catalyst for ethylene glycol fuel cells and a preparation method thereof, and belongs to the technical field of electrocatalytic materials. The invention composites a SiOx@C pre-product with a covalent organic framework COFs by a solution method, then introduces metal atoms by a solution method, and finally forms a catalyst SiOx@C‑COF‑PtCoFe by high temperature treatment. The covalent organic framework COFs of the invention combines the electrical conductivity of SiOX@C with the synergistic effect of platinum, iron, and cobalt metal atoms, solves the problems of poor electrical conductivity and lack of active sites of pure COFs materials, and significantly enhances the electrocatalytic reaction ability. The catalyst has a stable structure, a high specific surface area, and many active sites, and is applied in the ethylene glycol oxidation reaction (EGOR) to show high electrocatalytic activity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of electrocatalytic materials, and in particular relates to a catalyst for ethylene glycol fuel cells and a preparation method thereof. Background Art

[0002] In recent years, in order to solve the problems of environmental pollution and energy crisis, the development of new energy and the search for excellent energy conversion devices have become the focus of research. Direct Ethylene Glycol Fuel Cell (DEGFC) is a fuel cell that uses ethylene glycol as fuel. Ethylene glycol is a substance widely present in life, with the advantages of low cost, high energy density, easy storage and transportation, so it is regarded as a potential fuel cell fuel. The working principle of ethylene glycol fuel cells is similar to that of other fuel cells, that is, ethylene glycol and oxygen are converted into electrical energy through electrochemical reactions. In the fuel cell, ethylene glycol is oxidized at the anode to release electrons and hydrogen ions (protons), while oxygen combines with hydrogen ions and electrons at the cathode to form water. In this process, electrons flow through the external circuit to generate current and provide power for the device. Due to the high density and molecular weight of ethylene glycol, the permeability of the membrane is small and the toxicity is also low. In addition, the most significant feature of ethylene glycol in the medium solution is that the electro-oxidation-reduction reaction is fast and can show good electro-oxidation performance. Therefore, the selection of ethylene glycol as the fuel for fuel cells has attracted widespread attention from scientists around the world.

[0003] Fuel cells are devices that convert chemical energy into electrical energy with the help of electrocatalysts, which can reduce the reaction barrier and thus carry out oxidation and reduction processes more efficiently. However, the anode kinetics of fuel cells are slow and require highly active anode catalysts to promote them. Therefore, how to quickly develop efficient catalysts has been the mainstream of research in this field in recent years. Platinum-based catalysts are currently the most important catalysts used in fuel cell anodes, but factors such as the scarcity of precious metals and weak anti-poisoning ability have severely limited the further application of fuel cells. Therefore, how to introduce non-Pt substances into the catalyst to reduce costs while maintaining good catalytic performance has always been a hot topic and difficulty in research in this field. Summary of the invention

[0004] In view of the shortcomings and disadvantages of the existing catalyst material technology, the purpose of the present invention is to provide a catalyst for ethylene glycol fuel cells and a preparation method thereof. The catalyst has a stable structure, a high specific surface area, and a large number of active sites, which not only reduces the preparation cost of the precious metal catalyst, but also exhibits a high electrocatalytic activity in the ethylene glycol oxidation reaction.

[0005] The present invention provides a method for preparing a catalyst for an ethylene glycol fuel cell, comprising the following steps:

[0006] S1: Add melamine phosphate, trialdehyde pyrogallol, 1,3,5-tris(4-aminophenoxy)benzene and SiOx@C pre-product into an organic solution, ultrasonicate to obtain a mixed solution, then add anhydrous acetic acid as a catalyst, transfer the mixed solution into an oil bath, reflux at 180-200°C for 2-4h, centrifuge after the reaction, wash with dimethyl sulfoxide and deionized water, and dry to obtain a powdered solid; the COFs material generated in this step is nano-microsphere with a particle size of 20-50nm, which has a very high specific surface area, abundant active sites and good electron transmission channels, and can effectively promote chemical reactions in fuel cells and improve battery performance. At the same time, since melamine phosphate contains N and P, the generated COFs have ultra-high N and P doping levels. At the same time, the hollow structure of SiOx@C pre-product and nitrogen-doped COFs will form a stable CN structure, which can maintain long-term stability in acidic or alkaline electrolytes. In addition, the COFs have a very high surface energy and are not easy to agglomerate, resulting in full exposure of the active sites and greatly improved product performance.

[0007] S2: Dissolve the powdered solid in acetonitrile, add the metal salt solution, disperse it ultrasonically, and then stir vigorously to fully react; after the reaction, centrifuge, vacuum dry and cool, and finally place it in a tubular furnace for calcination. Heat it to 600-800℃ at a rate of 5-10℃ / min under the protection of flowing high-purity argon, keep it warm for 1-2 hours, and then cool it naturally to obtain the catalyst. During the high-temperature calcination process, the introduced metal atoms form a stable PtCoFe-NC structure, and the platinum, cobalt and iron atoms are highly dispersed; at the same time, the hollow structure SiO X @C The internal cavity of the pre-product gradually enlarged and broke, forming a porous SiO X @C, providing high porosity and large specific surface area, and exposing more catalytic active centers, which can provide fast transmission channels for charge carriers and improve the catalytic activity and stability of the material. In addition, after calcination, it was found that the carbon atoms around the introduced N and P atoms were activated by heteroatoms, enhancing their electrocatalytic activity.

[0008] Preferably, the SiOx@C pre-product is prepared by the following steps: dissolving 10g of terephthalaldehyde in 80-100mL of deionized water, stirring at 80-100°C for 1 hour, adding n-octyl triethoxysilane or isooctyl triethoxysilane dropwise, the molar ratio of terephthalaldehyde to n-octyl triethoxysilane or isooctyl triethoxysilane is 1:4, stirring for 30 minutes, centrifuging, washing with deionized water, and drying to obtain an intermediate product; then mixing the intermediate product, zinc powder and anhydrous aluminum chloride in a mass ratio of 1:1:10, heating to 300-350°C at a rate of 5-10°C / min under the protection of flowing high-purity argon, keeping warm for 10-12 hours, washing the product with hydrochloric acid and drying. Silane and aldehyde are subjected to an aldehyde-amine condensation reaction, and then a cavity is gradually formed inside the product during low-temperature calcination to obtain a hollow structure SiOx@C pre-product with a size range of 2-5μm.

[0009] Preferably, the mass ratio of melamine phosphate, trialdehyde phloroglucinol, 1,3,5-tris(4-aminophenoxy)benzene and SiOx@C in the mixed solution is 1-1.2:2:0.8-1:1-2.

[0010] Preferably, the concentration of acetic acid in the mixed solution is 1-3 mol / L.

[0011] Preferably, the frequency of the ultrasound is 20-40KHz, and the power is 50-200W.

[0012] Preferably, the organic solvent includes one of dimethyl sulfoxide, N,N-dimethylformamide and diisopropylethylamine.

[0013] Preferably, the mass ratio of the powdered solid to the metal salt is 1:0.1-5.

[0014] Preferably, the metal salt solution is an aqueous solution containing 0.05-0.2M platinum salt, 0.05-0.2M iron salt and 0.05-0.2M cobalt salt.

[0015] Preferably, the platinum salt is potassium platinum chloride, the iron salt is ferric nitrate, ferric chloride, ferric acetate or ferric sulfate, and the cobalt salt is cobalt nitrate, cobalt chloride, cobalt acetate or cobalt sulfate.

[0016] The present invention also provides a catalyst for ethylene glycol fuel cells prepared by the above method.

[0017] Beneficial effects:

[0018] The COFs prepared by the method of the present invention are nano-microspheres, have ultra-high N and P doping amounts and very high specific surface area, and have many active sites, which are the prerequisites for becoming efficient catalysts; in addition, the introduction of N and P elements not only improves the xThe conductivity of platinum-based catalysts also has a certain catalytic effect and anchoring effect on Pt in the catalyst, thereby improving the catalytic activity of the catalyst; in addition, COFs can enhance the conductivity of the catalyst by interacting with the porous hollow structure of SiO X @C forms a stable CN structure, thereby introducing SiO X @C has excellent electron transport performance, which enhances the transfer of electrons from the electrode to the catalytic sites of the COFs layer, solving the problem of poor conductivity of pure COFs materials. On the other hand, it can increase the loading of metal atoms (platinum, cobalt, iron) atoms, and avoid the aggregation and deactivation of metal atoms, solving the problem of the lack of active sites of pure COF materials as electrocatalysts. It can also deliver reactants and products to platinum atoms for catalysis through the enrichment of high specific surface area. The co-doping of these three metal atoms not only reduces the preparation cost of the catalyst, establishes a synergistic effect between elements, but also uses the lattice mismatch of different elements to induce a strain effect to reduce the D band of Pt, thereby increasing the reaction activation energy on the Pt surface. Compared with traditional commercial noble metal-free catalysts, the catalyst of the present invention significantly enhances the electrocatalytic reaction ability, and the EGOR catalytic performance is better than that of commercial catalysts, meeting the requirements of industrialization. DETAILED DESCRIPTION

[0019] The following specific examples are used to illustrate the embodiments of the present invention. Those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.

[0020] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.

[0021] Example 1

[0022] A method for preparing a catalyst for an ethylene glycol fuel cell comprises the following steps:

[0023] (1) 10 g of terephthalaldehyde was dissolved in 90 mL of deionized water, stirred at 80° C. for 1 hour, and n-octyltriethoxysilane was added dropwise, wherein the molar ratio of terephthalaldehyde to n-octyltriethoxysilane was 1:4. The mixture was stirred for 30 minutes, and the solution was drained under reduced pressure to obtain an intermediate product. The intermediate product, zinc powder and anhydrous aluminum chloride were mixed in a mass ratio of 1:3:10, and heated to 330° C. at a rate of 8° C. / min under the protection of flowing high-purity argon gas, and kept warm for 12 hours. The product was washed with hydrochloric acid and dried to obtain a SiOx@C pre-product.

[0024] (2) Melamine phosphate, trialdehyde pyrogallol, 1,3,5-tris(4-aminophenoxy)benzene and SiOx@C pre-product were added to the organic solution dimethyl sulfoxide in a mass ratio of 1.1:2:0.9:1.5, and ultrasonicated for 10 min at room temperature at a frequency of 30 kHz and a power of 10 W to obtain a mixed solution. Anhydrous acetic acid was then added as a catalyst to control the concentration of acetic acid in the mixed solution to 2 mol / L. The mixed solution was then transferred to an oil bath and refluxed at 190°C for 3 h. After the reaction was completed, the mixture was centrifuged, washed with dimethyl sulfoxide and deionized water, and dried to obtain a powdered solid SiOx@C-COF.

[0025] (3) The powdered solid was dissolved in acetonitrile, and a metal salt solution (containing 0.2 M potassium platinum chloride, 0.2 M ferric chloride and 0.2 M cobalt acetate in water, water temperature 90°C) was added, the mass ratio of the powdered solid to the metal salt was 1:2, and then ultrasonically dispersed at a frequency of 30 kHz and a power of 100 W for 10 min, and then vigorously stirred for sufficient reaction; after the reaction was completed, centrifuged, vacuum dried and cooled, and finally placed in a tubular furnace for calcination and heat treated at 700°C for .5 hours under the protection of flowing high-purity argon gas, and then naturally cooled to obtain the SiOx@C-COF-PtCoFe catalyst.

[0026] The SiOx@C-COF-PtCoFe catalyst prepared in Example 1 was applied to EGOR in DEGFC. In order to evaluate the performance and stability of the catalyst, a series of electrochemical tests were carried out, and the catalyst was also assembled into a DEGFC cell reactor for practical application testing.

[0027] The electrochemical test results show that SiOx@C-COF-PtCoFe has a low peak potential for EGOR of 0.47 V, which is 100 mV lower than the reference value of Pt / C (0.57 V). In addition, after ethylene glycol oxidation test, its EGOR activity is 0.882 A mg -1 PtCoFe , is Pt / C(0.221A mg -1 Pt ). After the 3000s chronoamperometric stability test, the residual current density was 0.055A mg -1 PtCoFe After 500 cycles of cycle stability testing, the peak current retention rate was 86.4%. When SiOx@C-COF-PtCoFe was finally used as the anode catalyst to assemble DEGFC, the OCV (0.57V) and maximum current density (0.097A cm -2 ) and maximum power density (9.21mW cm -2) are higher than commercial Pt / C (OCV (0.52V), maximum current density (0.080A cm -2 ) and maximum power density (6.00mWcm -2 ).

[0028] Example 2

[0029] A method for preparing a catalyst for an ethylene glycol fuel cell comprises the following steps:

[0030] (1) 10 g of terephthalaldehyde was dissolved in 80 mL of deionized water, stirred at 80° C. for 1 hour, and n-octyltriethoxysilane was added dropwise, wherein the molar ratio of terephthalaldehyde to n-octyltriethoxysilane was 1:4. The mixture was stirred for 30 minutes, and the solution was drained under reduced pressure to obtain an intermediate product. The intermediate product, zinc powder and anhydrous aluminum chloride were mixed in a mass ratio of 1:3:10, and heated to 300° C. at a rate of 5° C. / min under the protection of flowing high-purity argon gas, and kept warm for 10 hours. The product was washed with hydrochloric acid and dried to obtain a SiOx@C pre-product.

[0031] (2) Melamine phosphate, trialdehyde pyrogallol, 1,3,5-tris(4-aminophenoxy)benzene and SiOx@C pre-product were added to the organic solution dimethyl sulfoxide in a mass ratio of 1:2:1:1, and ultrasonicated for 10 min at room temperature at a frequency of 20 kHz and a power of 50 W to obtain a mixed solution. Anhydrous acetic acid was then added as a catalyst to control the concentration of acetic acid in the mixed solution to be 1 mol / L. The mixed solution was then transferred to an oil bath and refluxed at 180°C for 2 h. After the reaction was completed, the mixture was centrifuged, washed with dimethyl sulfoxide and deionized water, and dried to obtain a powdered solid SiOx@C-COF.

[0032] (3) The powdered solid was dissolved in acetonitrile, and a metal salt solution (containing 0.2 M potassium platinum chloride, 0.2 M ferric chloride and 0.2 M cobalt chloride in water, water temperature 90°C) was added, the mass ratio of the powdered solid to the metal salt was 1:0.1, and then ultrasonically dispersed at a frequency of 20 kHz and a power of 50 W for 10 min, and then vigorously stirred for sufficient reaction; after the reaction was completed, centrifuged, vacuum dried and cooled, and finally placed in a tubular furnace for calcination and heat treated at 600°C for 1 hour under the protection of flowing high-purity argon gas, and then naturally cooled to obtain the SiOx@C-COF-PtCoFe catalyst.

[0033] Example 3

[0034] A method for preparing a catalyst for an ethylene glycol fuel cell comprises the following steps:

[0035] (1) 10 g of terephthalaldehyde is dissolved in 100 mL of deionized water, stirred at 80° C. for 1 hour, and n-octyltriethoxysilane or isooctyltriethoxysilane is added dropwise, wherein the molar ratio of terephthalaldehyde to n-octyltriethoxysilane or isooctyltriethoxysilane is 1:4, stirred for 30 minutes, and the solution is drained under reduced pressure to obtain an intermediate product; then the intermediate product, zinc powder and anhydrous aluminum chloride are mixed in a mass ratio of 1:3:10, heated to 350° C. at a rate of 10° C. / min under the protection of flowing high-purity argon gas, and kept warm for 12 hours, and the product is washed with hydrochloric acid and dried to obtain a SiOx@C pre-product.

[0036] (2) Melamine phosphate, trialdehyde pyrogallol, 1,3,5-tris(4-aminophenoxy)benzene and SiOx@C pre-product were added to the organic solution dimethyl sulfoxide in a mass ratio of 1.2:2:0.8:2, and ultrasonicated for 10 min at room temperature at a frequency of 20-40 kHz and a power of 50-200 W to obtain a mixed solution. Anhydrous acetic acid was then added as a catalyst to control the concentration of acetic acid in the mixed solution to 3 mol / L. The mixed solution was then transferred to an oil bath and refluxed at 200°C for 4 h. After the reaction was completed, the mixture was centrifuged, washed with dimethyl sulfoxide and deionized water, and dried to obtain a powdered solid SiOx@C-COF.

[0037] (3) The powdered solid was dissolved in acetonitrile, and a metal salt solution (containing 0.2 M potassium platinum chloride, 0.2 M ferric chloride and 0.2 M cobalt acetate in water, water temperature 90°C) was added, the mass ratio of the powdered solid to the metal salt was 1:5, and then ultrasonically dispersed at a frequency of 40 kHz and a power of 200 W for 10 min, and then vigorously stirred for sufficient reaction; after the reaction was completed, centrifuged, vacuum dried and cooled, and finally placed in a tubular furnace for calcination and heat treated at 800°C for 2 hours under the protection of flowing high-purity argon gas, and then naturally cooled to obtain the SiOx@C-COF-PtCoFe catalyst.

[0038] Comparative Example 1

[0039] As described in Example 1, except that step (1) was omitted and no SiOx@C pre-product was added in step (2). The other steps and conditions were the same as in Example 1. It was found that after the ethylene glycol oxidation test, its EGOR activity was 0.362 A mg -1 PtCoFe After 500 cycles of cyclic stability testing, the peak current retention rate was 36.8%, indicating that the catalytic performance of the catalyst prepared by this method is poor.

[0040] Comparative Example 2

[0041] As described in Example 1, except that step (2) was omitted and in step (3), the SiOx@C pre-product was substituted for the powdered solid SiOx@C-COF and dissolved in acetonitrile. The other steps and conditions were the same as in Example 1. It was found that after the ethylene glycol oxidation test, its EGOR activity was 0.459 A mg -1 PtCoFe After 500 cycles of cycle stability testing, the peak current retention rate was 43.4%, indicating that the catalytic performance of the catalyst prepared by this method is very poor.

[0042] Comparative Example 3

[0043] As described in Example 1, except that melamine was used in step (2) to replace melamine phosphate. The other steps and conditions were the same as in Example 1. It was found that after the ethylene glycol oxidation test, its EGOR activity was 0.532 A mg -1 PtCoFe After 500 cycles of cycle stability testing, its peak current retention rate was 66.4%, indicating that the catalytic performance and durability of the catalyst were very poor.

[0044] The present invention has a unique structure, rich pores, a high amount of N and P heteroatom doping, and the interaction of various metal elements, which show a good synergistic effect and can improve the activity and durability of the catalyst. In other words, the atomic ratio of the noble metal in the catalyst is greatly reduced, the utilization rate of the noble metal is improved, and the production cost of the catalyst is further reduced. In addition, the defect of easy agglomeration of metal atoms in metal-based catalysts is overcome, so it has excellent stability (the current density retention rate is still maintained at more than 90% after 48 hours), and the catalyst can be successfully applied to ethylene glycol fuel cells.

[0045] The preferred specific implementation modes and embodiments of the present invention are described in detail above, but the present invention is not limited to the above implementation modes and embodiments, and various changes can be made within the knowledge scope of those skilled in the art without departing from the concept of the present invention.

Claims

1. A method for preparing a catalyst for an ethylene glycol fuel cell, characterized in that: The following steps are involved: S1: Add melamine phosphate, trialdehyde phloroglucinol, 1,3,5-tris(4-aminophenoxy)benzene and SiOx@C pre-product into an organic solution, perform ultrasonic treatment to obtain a mixed solution, then add anhydrous acetic acid as a catalyst, transfer the mixed solution into an oil bath, reflux at 180-200°C for 2-4 h, centrifuge after the reaction, wash with dimethyl sulfoxide and deionized water, and dry to obtain a powdery solid; S2: dissolving the powdered solid in acetonitrile, adding the metal salt solution, ultrasonically dispersing, and then vigorously stirring for a full reaction; after the reaction, centrifuging, vacuum drying, and cooling, finally placing in a tubular furnace for calcination, heating to 600-800°C at a rate of 5-10°C / min under the protection of flowing high-purity argon, keeping warm for 1-2 hours, and naturally cooling to obtain the catalyst; The SiOx@C pre-product is prepared by the following steps: dissolving 10 g of terephthalaldehyde in 80-100 mL of deionized water, stirring at 80-100° C. for 1 hour, adding n-octyl triethoxysilane or isooctyl triethoxysilane dropwise, wherein the molar ratio of terephthalaldehyde to n-octyl triethoxysilane or isooctyl triethoxysilane is 1:4, stirring for 30 minutes, centrifuging, washing with deionized water, and drying to obtain an intermediate product; then mixing the intermediate product, zinc powder, and anhydrous aluminum chloride in a mass ratio of 1:1:10, heating to 300-350° C. at a rate of 5-10° C. / min under the protection of flowing high-purity argon, keeping the temperature for 10-12 hours, washing the product with hydrochloric acid, and drying; The metal salt solution is an aqueous solution containing 0.05-0.2M platinum salt, 0.05-0.2M iron salt and 0.05-0.2M cobalt salt.

2. The method according to claim 1, characterized in that: The mass ratio of melamine phosphate, trialdehyde phloroglucinol, 1,3,5-tris(4-aminophenoxy)benzene and SiOx@C in the mixed solution is 1-1.2: 2: 0.8-1: 1-2.

3. The method according to claim 1, characterized in that: The concentration of acetic acid in the mixed solution is 1-3 mol / L.

4. The method according to claim 1, characterized in that: The frequency of the ultrasound is 20-40KHz, and the power is 50-200W.

5. The method according to claim 1, characterized in that: The organic solvent includes one of dimethyl sulfoxide, N,N-dimethylformamide and diisopropylethylamine.

6. The method according to claim 1, characterized in that: The mass ratio of the powdered solid to the metal salt is 1:0.1-5.

7. The method according to claim 1, characterized in that: The platinum salt is potassium platinum chloride, the iron salt is iron nitrate, iron chloride, iron acetate or iron sulfate, and the cobalt salt is cobalt nitrate, cobalt chloride, cobalt acetate or cobalt sulfate.

8. A catalyst for ethylene glycol fuel cells prepared by the method according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Application method of carbon-nitrogen doped indium oxide semiconductor photocatalytic material in preparation of hydrogen

    CN111871437A

  • COF (at) Pd composite nano-enzyme and preparation method thereof

    CN117224701A